Quality indicators for micrografted seedlings of Theobroma cacao inoculated with arbuscular mycorrhizal fungi - Pérez-Díaz, Alberto; Aranda-Azaharez, Raúl; Rivera-Espinosa, Ramón Antonio; Bustamante-González, Carlos Alberto; Pérez-Suarez, Yasmin (Agronomía Mesoamericana, 2023)
Introduction. For the proper establishment of cocoa plantations, suitable technologies must be guaranteed to obtain quality seedlings (young plants sown and developed in bags) in the nurseries. Objective. To define quality indicators for cocoa seedlings produced via micro-grafting, depending on organic sources and arbuscular mycorrhizal fungi in a Brown Sialitic soil. Materials and methods. Between 2018 and 2019 in the nursery of the Empresa Agroforestal y Coco de Baracoa, the inoculation of the Glomus cubense and Rhizoglomus irregulare strains in substrates formed by earthworm humus and composted cocoa husk (3:1,5:1 v/v) was evaluated. A completely randomized design was used, with 50 postures per treatment, of which 25 were evaluated. At four months, the following were evaluated: plant height, stem diameter, aerial, root and total dry mass, foliar nutrient concentration (N, P, K), leaf area, slenderness index, Dickson Quality Index (DQI), and the percentage of mycorrhizal colonization. A simple rank analysis of variance was performed and Duncan’s comparison test (95 %) was applied. Results. The inoculation of G. cubense and R. irregulare, regardless of the source, significantly increased total dry mass (39 %), the leaf area (20 %) and the DQI (48 %) with respect to the controls. The DQI was significantly related (p<0.05) to total dry mass and leaf area (R2= 0.97). The inoculation with R. irregulare and G. cubense increased the leaf N, P, and k concentrations. Conclusions. The variables total dry mass, leaf area, slenderness index, and DQI showed an integrative character of plant growth and can be used as quality indicators for cocoa micro-grafts, based on soil : organic fertilizer relationships and inoculation with G. cubense and R. irregulare.